Composite tin dioxide layer used in perovskite cell, preparation method of composite tin dioxide layer and perovskite solar cell
By combining the tin dioxide layers obtained by deposition of different oxygen sources in perovskite solar cells, a composite tin dioxide layer is formed, which solves the membrane structure defects and performance limitations of the ALD-SnO2 film in perovskite solar cells, and significantly improves the performance indicators of the battery.
Patent Information
- Application Number
- CN202411994905.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
AI Technical Summary
At this stage, ALD-SnO2 films have membrane structural defects and performance limitations in perovskite solar cells, and cannot take into account all performances, and there is room for improvement in application efficiency.
Through the atomic layer deposition technology, the tin dioxide layer obtained by deposition of different oxygen sources (water, ozone or plasma activated oxygen) is combined to form a composite tin dioxide layer to make up for the defects of the single oxygen source deposition film, and take into account the advantages of each tin dioxide layer.
The film quality of the composite tin dioxide layer is improved, and the open circuit voltage, filling factor and energy conversion efficiency of perovskite solar cells are enhanced. Specifically, the short circuit current is increased to 0.510A-0.518A, the open circuit voltage reaches 44.70V-44.90V, the filling factor is between 0.699-0.722, and the energy conversion efficiency can reach 17.95%-18.74%.
Smart Images

Figure CN119836199A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of perovskite solar cell preparation, and in particular to a composite tin dioxide layer used in a perovskite cell, a preparation method thereof, and a perovskite solar cell. Background Art
[0002] Tin dioxide thin films are widely used in many fields such as transparent conductive materials, optoelectronic devices or sensors due to their unique physical and chemical properties. Therefore, in order to meet the needs of different fields, there are various methods for preparing tin dioxide thin films. Common preparation methods include spin coating, sputtering, pulsed laser deposition, chemical bath deposition (CBD), chemical vapor deposition (CVD) and atomic layer deposition (ALD). ALD is considered to be one of the best thin film growth technologies. In addition to microelectronic applications, its application range also includes the development of biosensors, protective coatings, and energy conversion and storage. It mainly controls the fine growth of thin films at the atomic level by passing precursors into the chamber in a cycle to react. In addition, ALD technology is also fully compatible with flexible substrates / devices, so it has gradually received more and more research and attention.
[0003] In the field of tin dioxide film preparation, due to the unique advantages of ALD technology, the application fields of the prepared tin dioxide films are constantly being expanded. Compared with other tin dioxide film deposition technologies, ALD can deposit pinhole-free, uniform and highly three-dimensional conformal films at a relatively low temperature, and has the characteristics of precise control of film thickness and large-area growth.
[0004] At present, the tin dioxide film prepared by ALD technology has been widely used in perovskite solar cells. It can be used as the electron transport layer of the formal battery device (substrate / transparent electrode layer / ALD-SnO2 / perovskite / hole transport layer / top electrode), and can also be used as the reverse battery device (substrate / transparent electrode layer / hole transport layer / perovskite / C 60 / ALD-SnO2 / top electrode) buffer layer. However, at this stage, ALD-SnO2 films are all deposited by the reaction of a certain oxygen source and tin source, where the oxygen source includes a single water (H2O), a single oxygen (O3) or a single oxygen plasma (Oplasma), etc., and the tin source includes Sn(C2H6N)4, etc. The films prepared by different oxygen sources have different physical and chemical properties, each with its own advantages and disadvantages, which will cause different defects in the prepared film structure. In addition, the ALD-SnO2 film prepared by a single oxygen source also has limitations in practical applications, and it is impossible to take into account various performances. In addition, the efficiency of perovskite solar cell devices prepared by ALD-SnO2 still has a lot of room for improvement.
[0005] Therefore, how to improve the quality of the tin dioxide layer prepared by ALD technology, reduce internal structural defects to obtain a complete crystal structure, and then improve the performance of perovskite solar cells has become a problem that needs to be solved urgently. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a composite tin dioxide layer for use in a perovskite cell, a preparation method thereof, and a perovskite solar cell. The composite tin dioxide layer of the present invention combines tin dioxide layers deposited using different oxygen sources, making up for the film structure defects and physical and chemical property disadvantages of the tin dioxide layer deposited using a single oxygen source, and after the combination, the advantages of each tin dioxide layer can be taken into account, and the complementary advantages improve the film quality of the prepared composite tin dioxide layer, which can be used in a perovskite solar cell to further improve the open circuit voltage, fill factor, energy conversion efficiency and other performance.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a composite tin dioxide layer for use in a perovskite cell, the preparation method comprising the following steps: depositing at least two stacked tin dioxide layers by atomic layer deposition technology;
[0009] The deposition raw materials of each tin dioxide layer independently include an oxygen source and a tin source, and the oxygen sources used by two adjacent tin dioxide layers are different in type; in the composite tin dioxide layer, the thickness of each tin dioxide layer is independently ≥1 nm.
[0010] In the present invention, tin dioxide layers deposited by different oxygen sources are combined to obtain a composite tin dioxide layer, which makes up for the film structure defects of the tin dioxide layer deposited by a single oxygen source, thereby avoiding defects capturing electrons in the perovskite solar cell, resulting in greater loss of battery performance, and especially avoiding a greater impact on the fill factor of the device; and by combining different tin dioxide layers deposited by different oxygen sources, the advantages of the tin dioxide layers deposited by various oxygen sources can be taken into account, and the advantages are complementary, that is, the film structure defects can be greatly reduced, and the reduction of the band gap can be avoided, etc., thereby improving the overall film quality of the composite tin dioxide layer, and using it in a perovskite solar cell can improve the performance such as open circuit voltage, fill factor and energy conversion efficiency.
[0011] As a preferred technical solution of the present invention, the oxygen source includes any one of water, ozone or plasma-activated oxygen.
[0012] Preferably, when depositing the first tin dioxide layer, the oxygen source is water.
[0013] It should be noted that in the present invention, since water has a relatively mild performance when used as an oxygen source, water is usually used as an oxygen source to deposit the first layer of tin dioxide, which is in direct contact with the perovskite to reduce the impact of the composite tin dioxide layer on the perovskite.
[0014] Preferably, when depositing at least three stacked tin dioxide layers, the deposition of three tin dioxide layers is considered as one deposition process. When the number of deposition groups is 1, the type of oxygen source used in each tin dioxide layer is different. When the number of deposition groups is greater than 1, the type of oxygen source used in each tin dioxide layer is different, and the types of oxygen source used in the two adjacent tin dioxide layers in each group are different.
[0015] It should be noted that the composite tin dioxide layer in the present invention may include two stacked tin dioxide layers, and may also include at least three stacked tin dioxide layers. When the composite tin dioxide layer includes two stacked tin dioxide layers, they are respectively the first tin dioxide layer-tin dioxide layer A and the second tin dioxide layer-tin dioxide layer B, and the oxygen sources used by the two are different, and there is no specific requirement or special limitation on the order of the two. Adaptive selection and adjustment can be made according to the actual application to meet the application under different conditions. It is preferred to use water as the oxygen source for the first tin dioxide layer; when the composite tin dioxide layer includes at least three stacked tin dioxide layers, when there are only three layers, they are respectively the first tin dioxide layer-tin dioxide layer A, the second tin dioxide layer-tin dioxide layer B and the third tin dioxide layer-tin dioxide layer C, and the oxygen sources used by the three are different, and There are no specific requirements or special limitations on the order of the three, and they can be adaptively selected and adjusted according to actual applications to meet the application under different conditions. Preferably, water is used as the oxygen source for the first tin dioxide layer; when there are ≥3 layers, they are the first tin dioxide layer-tin dioxide layer A, the second tin dioxide layer-tin dioxide layer B and the third tin dioxide layer-tin dioxide layer C, and the above three-layer structure is a group. There are no specific requirements or special limitations on the order of the three, and they can be adaptively selected and adjusted according to actual applications to meet the application under different conditions. In addition, the types of oxygen sources used by the two adjacent tin dioxide layers in each group are different. Preferably, water is used as the oxygen source for the first tin dioxide layer in the first group.
[0016] As a preferred technical solution of the present invention, the tin source includes any one of alkyl tin, tin alkoxide or tetrakis(dimethylamino)tin or a combination of at least two thereof, preferably tetrakis(dimethylamino)tin.
[0017] Preferably, in the composite tin dioxide layer, the thickness of each layer is independently 2nm-15nm, for example, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm or 15nm.
[0018] In the present invention, the thickness of each layer of the regulated composite tin dioxide layer is 2nm-15nm, which can ensure that each layer can play its advantageous role to the maximum extent on the one hand, and on the other hand, it also avoids the thickness of each layer being too thick, which makes the overall thickness too thick, resulting in excessive resistance and reduced conductivity, which affects the efficiency of perovskite batteries when used.
[0019] Preferably, the total thickness of the composite tin dioxide layer is 10 nm-40 nm, for example, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm or 40 nm.
[0020] In the present invention, the total thickness of the composite tin dioxide layer is regulated to be 10nm-40nm, so that the perovskite solar cell has a higher open circuit voltage, fill factor and energy conversion efficiency. If it is too thick, the conductivity of the material will be reduced, which will lead to the problem of reduced fill factor and energy conversion efficiency, and will also cause energy level mismatch and reduced electron transmission efficiency. If it is too thin, it cannot effectively cover interface defects, and may also increase contact resistance and carrier recombination rate, thereby affecting battery performance.
[0021] As a preferred technical solution of the present invention, the step of depositing at least two stacked tin dioxide layers by atomic layer deposition technology comprises:
[0022] The tin source is introduced and purged with an inert gas, and then the oxygen source is introduced and purged with an inert gas, so that the tin source and the oxygen source react. This is one cycle. After multiple cycles, the first tin dioxide layer is obtained. Then the type of the oxygen source is replaced and the above process is repeated to obtain at least two stacked tin dioxide layers.
[0023] As a preferred technical solution of the present invention, the tin source is introduced through the inert gas as a carrier gas, and the flow rate of the carrier gas is 50sccm-250sccm, for example, 50sccm, 80sccm, 100sccm, 120sccm, 150sccm, 180sccm, 200sccm, 220sccm or 250sccm, etc.
[0024] Preferably, the introduction time of the tin source is 0.1s-0.6s, for example, 0.1s, 0.2s, 0.3s, 0.4s, 0.5s or 0.6s.
[0025] As a preferred technical solution of the present invention, the oxygen source is introduced through the inert gas as a carrier gas, and the flow rate of the carrier gas is 50sccm-250sccm, for example, 50sccm, 80sccm, 100sccm, 120sccm, 150sccm, 180sccm, 200sccm, 220sccm or 250sccm, etc.
[0026] Preferably, when water is used as the oxygen source, the water is introduced for a time of 0.2s-1.8s, for example, 0.2s, 0.4s, 0.6s, 0.8s, 1.0s, 1.2s, 1.4s, 1.6s or 1.8s.
[0027] Preferably, when ozone is used as the oxygen source, the ozone is introduced for 4s-12s, for example, 4s, 5s, 6s, 7s, 8s, 9s, 10s, 11s or 12s.
[0028] Preferably, when the oxygen source is plasma-activated oxygen, the introduction time of the plasma-activated oxygen is 4s-12s, for example, 4s, 5s, 6s, 7s, 8s, 9s, 10s, 11s or 12s.
[0029] In the present invention, the introduction time of the water is regulated to be 0.2s-1.8s, the introduction time of the ozone is 4s-12s, and the introduction time of the plasma-activated oxygen is 4s-12s, so that the tin dioxide layers deposited respectively can have better performance. If the introduction time of the ozone and the plasma-activated oxygen is too short, the deposition of the tin dioxide layers respectively obtained will be uneven, the oxygen vacancies will increase, and the defects of the film structure of the composite tin dioxide layer will increase. If it is applied to perovskite solar cells, the overall performance of the battery will be reduced.
[0030] Preferably, the number of the multiple cycles is 10-150 times, for example 10 times, 20 times, 50 times, 80 times, 100 times, 120 times or 150 times, etc.
[0031] Preferably, the flow rate of the inert gas purge is 50 sccm-250 sccm, for example, 50 sccm, 80 sccm, 100 sccm, 120 sccm, 150 sccm, 180 sccm, 200 sccm, 220 sccm or 250 sccm, etc.
[0032] Preferably, the inert gas purging time is 5s-15s, for example, 5s, 8s, 10s, 12s or 15s.
[0033] Preferably, the inert gas comprises argon or nitrogen.
[0034] In a second aspect, the present invention further provides a composite tin dioxide layer, which is prepared according to the preparation method described in the first aspect.
[0035] In a third aspect, the present invention further provides a perovskite solar cell buffer layer, wherein the perovskite solar cell buffer layer comprises the composite tin dioxide layer as described in the second aspect.
[0036] In a fourth aspect, the present invention further provides a perovskite solar cell electron transport layer, wherein the perovskite solar cell electron transport layer comprises the composite tin dioxide layer as described in the second aspect.
[0037] In a fifth aspect, the present invention further provides a perovskite solar cell, wherein the perovskite solar cell comprises the perovskite solar cell buffer layer as described in the third aspect and / or the perovskite solar cell electron transport layer as described in the fourth aspect.
[0038] As a preferred technical solution of the present invention, the perovskite solar cell includes sub-cells connected in series.
[0039] As a preferred technical solution of the present invention, the sub-cell includes a cathode conductive substrate, a hole transport layer, a perovskite light absorption layer, an electron transport layer, a buffer layer and a conductive anode layer stacked in sequence, and the buffer layer includes the perovskite solar cell buffer layer as described in the third aspect.
[0040] Preferably, the cathode conductive substrate comprises a substrate and a conductive cathode layer located on one side surface of the substrate.
[0041] It should be noted that the present invention does not impose any specific requirements or special limitations on the material type of the substrate. As long as it is a type commonly used by technicians in this field, it is applicable to the present invention, for example, it can be a glass plate, a silicon wafer, a PET plate or a PI plate.
[0042] It should be noted that the present invention does not impose any specific requirements or special limitations on the type of material of the conductive cathode layer. As long as it is a type commonly used by those skilled in the art, it is applicable to the present invention, for example, it may be ITO, FTO or Ag nanowire.
[0043] Preferably, the thickness of the conductive cathode layer is 500 nm-1000 nm, for example, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm or 1000 nm.
[0044] It should be noted that the present invention does not make any specific requirements or special restrictions on the material type of the hole transport layer. As long as it is a type commonly used by those skilled in the art, it is applicable to the present invention. For example, it can be NiO x, Cu2O, P3HT, PTAA or Spiro-OMeTAD.
[0045] Preferably, the hole transport layer has a thickness of 10 nm-200 nm, for example, 10 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm or 200 nm.
[0046] Preferably, the material layer of the perovskite light absorbing layer includes ABX3 type perovskite material.
[0047] Preferably, A is any one of cesium ion, rubidium ion, methylamine group or formamidinium group, or a combination of at least two of them.
[0048] Preferably, B is lead ion and / or tin ion.
[0049] Preferably, X is any one of bromide ion, iodide ion or chloride ion, or a combination of at least two of them.
[0050] Preferably, the thickness of the perovskite light absorbing layer is 200 nm-600 nm, for example, 200 nm, 300 nm, 400 nm, 500 nm or 600 nm.
[0051] It should be noted that the present invention does not make any specific requirements or special restrictions on the type of material of the electron transport layer. As long as it is a type commonly used by those skilled in the art, it is applicable to the present invention. For example, it can be C 60 , TiO2, SnO2, ZnO or PC 61 Any one of BM.
[0052] Preferably, the thickness of the electron transport layer is 10 nm-50 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm or 50 nm.
[0053] It should be noted that the present invention does not make any specific requirements or special limitations on the type of material of the conductive anode layer. As long as it is a type commonly used by technicians in this field, it is applicable to the present invention, for example, it can be any one of Au, Ag, Cu, Pt or C.
[0054] Preferably, the thickness of the conductive anode layer is 100 nm-200 nm, for example, 100 nm, 120 nm, 150 nm, 180 nm or 200 nm.
[0055] It should be noted that the method for preparing the perovskite solar cell of the present invention is a conventional method and can be adaptively selected and adjusted according to actual conditions.
[0056] Exemplarily, the present invention provides a method for preparing a perovskite solar cell, the preparation method comprising the following steps:
[0057] (1) providing a substrate, preparing a conductive cathode layer on one side of the substrate, laser-scribing the conductive cathode layer to form a first etching groove penetrating the conductive cathode layer, and cleaning the conductive cathode layer to obtain a cathode conductive substrate;
[0058] (2) In the cathode conductive substrate, a hole transport layer, a perovskite light absorption layer, an electron transport layer and a buffer layer are sequentially prepared on the surface of the conductive cathode layer;
[0059] (3) forming a second etching groove penetrating the hole transport layer, the perovskite light absorption layer, the electron transport layer and the buffer layer by laser scribing;
[0060] (4) preparing a conductive anode layer on the surface of the buffer layer, and forming a third etched groove penetrating the conductive anode layer by laser scribing to obtain a sub-battery;
[0061] (5) Repeating steps (1) to (4) to obtain multiple groups of sub-cells, and connecting the multiple groups of sub-cells in series to obtain the perovskite solar cell;
[0062] The method for preparing the perovskite light absorbing layer comprises the following steps: mixing the perovskite light absorbing layer material and an organic solvent to obtain a precursor solution with a concentration of 1 mol / L, placing the precursor solution on the surface of the hole transport layer to obtain the perovskite light absorbing layer.
[0063] It should be noted that the present invention does not make any specific requirements or special limitations on the method of placing the precursor solution on the surface of the hole transport layer. It can be adaptively selected and adjusted according to the different materials of the perovskite light absorbing layer. For example, it can be any one of solution spin coating, slit coating or inkjet printing.
[0064] It should be noted that the present invention does not make any specific requirements or special limitations on the organic solvent. As long as it is a type commonly used by technicians in this field, it is applicable to the present invention. For example, it can be any one of DMF, DMSO, isopropanol, chloroform, ethanol or methanol, or a combination of at least two of them.
[0065] It should be noted that the present invention does not make any specific requirements or special limitations on the preparation methods of the hole transport layer and the electron transport layer. As long as the preparation methods are commonly used by technicians in this field, they are applicable to the present invention. For example, it can be any one of spin coating, slit coating, inkjet printing, vacuum thermal deposition, electron beam evaporation, magnetron sputtering or atomic layer deposition.
[0066] It should be noted that the present invention does not make any specific requirements or special limitations on the preparation method of the conductive anode layer. As long as it is a preparation method commonly used by technicians in this field, it is applicable to the present invention, for example, it can be thermal evaporation or magnetron sputtering.
[0067] Compared with the prior art, the present invention has at least the following beneficial effects:
[0068] 1) The composite tin dioxide layer provided by the present invention combines tin dioxide layers deposited by different oxygen sources, thereby compensating for the film structure defects of the tin dioxide layer deposited by a single oxygen source, and the composite tin dioxide layer obtained by combining different tin dioxide layers can take into account the advantages of the tin dioxide layers deposited by various oxygen sources, and the complementary advantages improve the film quality.
[0069] 2) The composite tin dioxide layer provided by the present invention is used in a perovskite solar cell. Compared with the tin dioxide layer prepared by using a single oxygen source, the short-circuit current, open-circuit voltage, fill factor and energy conversion efficiency can be further improved. Among them, the short-circuit current can reach 0.510A-0.518A, the open-circuit voltage can reach 44.70V-44.90V, the fill factor can reach 0.699-0.722, and the energy conversion efficiency can reach 17.95%-18.74%. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 is a schematic diagram of the structure of the composite tin dioxide layer prepared in Example 1 of the present invention;
[0071] Among them, 1-H2O-SnO2 layer; 2-O3-SnO2 layer; 3-Oplasma-SnO2 layer. DETAILED DESCRIPTION
[0072] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0073] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0074] Example 1
[0075] This embodiment provides a method for preparing a composite tin dioxide layer for a perovskite cell, the preparation method comprising the following steps:
[0076] Place the substrate materials (including cathode conductive substrate, hole transport layer, perovskite light absorption layer and electron transport layer) into the ALD equipment and adjust the background vacuum of the equipment to less than 10-4 Torr, process vacuum 0.15 Torr, chamber temperature 100 ° C, first under the condition of argon as carrier gas, tetrakis(dimethylamino)tin is introduced into the reaction chamber, the introduction time is 0.1s, the carrier gas flow rate is 100sccm, and then it is purged with pure argon, the purge time is 10s, and the argon flow rate is 100sccm; then under the condition of argon as carrier gas, water is introduced into the reaction chamber, the introduction time is 0.6s, the carrier gas flow rate is 100sccm, and then it is purged with pure argon, the purge time is 10s, and the argon flow rate is 100sccm. Repeat the above steps 30 times to obtain a H2O-SnO2 layer with a thickness of 5nm using water as an oxygen source;
[0077] Subsequently, under the condition that argon is used as a carrier gas, tetrakis(dimethylamino)tin is introduced into the reaction chamber, the time of introduction is 0.1s, the carrier gas flow rate is 100sccm, and then it is purged with pure argon, the purging time is 10s, and the argon flow rate is 100sccm; then under the condition that argon is used as a carrier gas, ozone is introduced into the reaction chamber, the time of introduction is 5s, the carrier gas flow rate is 100sccm, and then it is purged with pure argon, the purging time is 10s, and the argon flow rate is 100sccm, and the above steps are repeated 30 times to obtain a 3nm thick O3-SnO2 layer with ozone as the oxygen source;
[0078] Subsequently, tetrakis(dimethylamino)tin was introduced into the reaction chamber under the condition of argon as a carrier gas, the introduction time was 0.1s, the carrier gas flow rate was 100sccm, and then it was purged with pure argon, the purging time was 10s, and the argon flow rate was 100sccm; then, under the condition of argon as a carrier gas, plasma-activated oxygen was introduced into the reaction chamber, the introduction time was 6s, the carrier gas flow rate was 100sccm, and then it was purged with pure argon, the purging time was 10s, and the argon flow rate was 100sccm, and the above steps were repeated 40 times to obtain a 5nm thick O plasma-SnO2 layer using plasma-activated oxygen as an oxygen source;
[0079] Furthermore, on the surface of the electron transport layer of the substrate material, a 5nmH2O-SnO2+3nmO3-SnO2+5nmO plasma-SnO2 composite tin dioxide layer buffer layer with a total thickness of 13nm was obtained.
[0080] Figure 1 The schematic diagram of the composite tin dioxide layer structure prepared in Example 1 of the present invention is shown. In order to make it easier to see the structure, each layer is set separately, but the structure actually prepared is a three-layer stacked structure with two layers combined with each other.
[0081] Example 2
[0082] This embodiment provides a method for preparing a composite tin dioxide layer for a perovskite cell, the preparation method comprising the following steps:
[0083] Place the substrate materials (including cathode conductive substrate, hole transport layer, perovskite light absorption layer and electron transport layer) into the ALD equipment and adjust the background vacuum of the equipment to less than 10 -4 Torr, process vacuum 0.15 Torr, chamber temperature 100 ° C, first under the condition of argon as carrier gas, tetrakis(dimethylamino)tin is introduced into the reaction chamber, the introduction time is 0.1s, the carrier gas flow rate is 100sccm, and then it is purged with pure argon, the purge time is 10s, and the argon flow rate is 100sccm; then under the condition of argon as carrier gas, water is introduced into the reaction chamber, the introduction time is 0.6s, the carrier gas flow rate is 100sccm, and then it is purged with pure argon, the purge time is 10s, and the argon flow rate is 100sccm. Repeat the above steps 39 times to obtain a H2O-SnO2 layer with a thickness of 6.5nm using water as an oxygen source;
[0084] Subsequently, tetrakis(dimethylamino)tin was introduced into the reaction chamber under the condition that argon was used as a carrier gas, the introduction time was 0.1s, the carrier gas flow rate was 100sccm, and then it was purged with pure argon, the purging time was 10s, and the argon flow rate was 100sccm; then, under the condition that argon was used as a carrier gas, plasma-activated oxygen was introduced into the reaction chamber, the introduction time was 6s, the carrier gas flow rate was 100sccm, and then it was purged with pure argon, the purging time was 10s, and the argon flow rate was 100sccm, and the above steps were repeated 52 times to obtain an O plasma-SnO2 layer with a thickness of 6.5nm using plasma-activated oxygen as an oxygen source;
[0085] Furthermore, a composite tin dioxide buffer layer of 6.5 nm H2O-SnO2+6.5 nm O plasma-SnO2 with a total thickness of 13 nm was obtained on the surface of the electron transport layer of the substrate material.
[0086] The structure of the composite tin dioxide layer of Example 3-9 is obtained by changing the parameters of the preparation method of Example 1. The specific changed parameters of Example 3-9 are shown in Table 1.
[0087] Table 1
[0088]
[0089] Note: "HS" stands for "H2O-SnO2 layer", "O3-S" stands for "O3-SnO2 layer", and "OS" stands for "O plasma-SnO2 layer"; " / " indicates that the corresponding oxygen source is not used and the corresponding layer structure is not set.
[0090] The structures of the composite tin dioxide layers of Comparative Examples 1-3 are prepared by changing the parameters of the method of Example 1. The specific changed parameters of Comparative Examples 1-3 are shown in Table 2.
[0091] Table 2
[0092]
[0093]
[0094] Note: "HS" stands for "H2O-SnO2 layer", "O3-S" stands for "O3-SnO2 layer", and "OS" stands for "O plasma-SnO2 layer"; " / " indicates that the corresponding oxygen source is not used and the corresponding layer structure is not set.
[0095] Application Example 1
[0096] This application example provides a perovskite solar cell and a preparation method thereof, wherein the perovskite solar cell comprises a cathode conductive substrate, a hole transport layer, a perovskite light absorption layer, an electron transport layer, a composite tin dioxide layer (buffer layer) of Example 1, and a conductive anode layer which are stacked in sequence;
[0097] The preparation method comprises the following steps:
[0098] (1) The composite tin dioxide layer of Example 1 is used as a buffer layer;
[0099] The substrate materials including the cathode conductive substrate, the hole transport layer, the perovskite light absorbing layer and the electron transport layer are prepared by the following method:
[0100] First, a fluorine-doped tin oxide (FTO) glass substrate was laser scribed to prepare a first etched groove, the FTO glass substrate was scrubbed with deionized water, and then ultrasonicated with deionized water, acetone and isopropanol for 15 minutes each to obtain a cathode conductive substrate; a 15 nm thick NiO layer was deposited on the surface of the cathode conductive substrate by magnetron sputtering. x Hole transport layer; CsI, FAI, MAI, PbI2, and PbBr2 were weighed in a nitrogen glove box according to the molar ratio. The perovskite component is Cs 0.05 MA 0.08 FA 0.87 Pb(I 0.92 Br 0.08 ), dissolved in a DMF:DMSO=9:1 solvent to obtain a precursor solution with a concentration of 1.0 mol / L, and a 400 nm thick perovskite light-absorbing layer was prepared on the surface of the hole transport layer by a slit coating method; a 20 nm thick C 60An electron transport layer is provided to obtain a substrate material;
[0101] (2) forming a second etching groove penetrating the hole transport layer, the perovskite light absorption layer, the electron transport layer and the buffer layer by laser scribing;
[0102] (3) a Cu layer with a thickness of 150 nm is deposited on the surface of the buffer layer by thermal evaporation as a conductive anode layer;
[0103] (4) laser scribing again to form a third etched groove penetrating the conductive anode layer to obtain a sub-cell;
[0104] (5) Repeat steps (1) to (4) to obtain 41 groups of sub-cells, and connect all the sub-cells in series to obtain the perovskite solar cell (aperture area of 896.875 cm 2 ).
[0105] Application Example 2-9 and Comparative Application Example 1-3
[0106] The composite tin dioxide layers prepared in Examples 2-9 and Comparative Examples 1-3 were respectively applied to the buffer layer of the perovskite solar cell. The specific structure and preparation method of the perovskite solar cell were consistent with those in Application Example 1, corresponding to Application Examples 2-9 and Comparative Application Examples 1-3, respectively.
[0107] The perovskite solar cells provided in Application Examples 1-9 and Comparative Application Examples 1-3 were tested for short-circuit current (Isc), open-circuit voltage (Voc), fill factor (FF) and energy conversion efficiency (Eff). The specific test results are shown in Table 3.
[0108] Table 3
[0109]
[0110]
[0111] The test results show that:
[0112] (1) It can be seen from Application Examples 1 to 5 that the present invention combines tin dioxide layers deposited using different oxygen sources to obtain a composite tin dioxide layer, which can take into account the advantages of each tin dioxide layer. The complementary advantages improve the film quality of the prepared composite tin dioxide layer, and the thickness of the composite tin dioxide is regulated within a suitable range and used in perovskite solar cells, which can further improve the open circuit voltage, fill factor, energy conversion efficiency and other performance. Specifically, the short circuit current can reach 0.510A-0.518A, the open circuit voltage can reach 44.70V-44.90V, the fill factor can reach 0.699-0.722, and the energy conversion efficiency can reach 17.95%-18.74%.
[0113] (2) It can be seen from Application Examples 1 and 6 to 7 that the present invention can better achieve that the tin dioxide layers deposited by each have better performance by further regulating the introduction time of the water to 0.2s-1.8s, the introduction time of the ozone to 4s-12s, and the introduction time of the plasma-activated oxygen to 4s-12s. If the introduction time of the ozone and the plasma-activated oxygen is too short, the deposition of the tin dioxide layers obtained by each will be uneven, resulting in an increase in oxygen vacancies and a large number of defects. Even if a composite tin dioxide layer is obtained by stacking different tin dioxide layer structures prepared from different oxygen sources, the defects of the membrane structure cannot be well optimized. When applied to perovskite solar cells, the overall performance of the battery will still be reduced, that is, the fill factor is reduced to 0.700 or less, and the efficiency is reduced to 17.83% or less.
[0114] (3) The present invention adjusts the thickness of each tin dioxide layer in the composite tin dioxide layer to 2nm-15nm, and at the same time makes the total thickness of the composite tin dioxide layer 10nm-40nm, so that the perovskite solar cell has a higher open circuit voltage, fill factor and energy conversion efficiency;
[0115] It can be seen from Application Examples 4 and 8 that in the buffer layer of Application Example 8, the O plasma-SnO2 layer is too thick, which makes the overall composite tin dioxide layer too thick, and the filling factor and energy conversion efficiency are reduced compared with those of Application Example 4;
[0116] It can be seen from Application Examples 1 and 9 that in the buffer layer of Application Example 9, while the thickness of the total composite tin dioxide layer remains consistent, the O plasma-SnO2 layer is too thin and cannot fully utilize the advantage of the high conductivity of the Oplasma-SnO2 layer. Therefore, the filling factor and energy conversion efficiency are reduced compared to those of Application Example 1.
[0117] (4) It can be seen from Application Example 1 and Comparative Application Examples 1 to Comparative Application Examples 3 that when only water is used as an oxygen source to prepare a tin dioxide layer of the same thickness in Comparative Application Example 1, more defects will be formed in the tin dioxide layer due to the water during the deposition process, which will capture electrons in the perovskite solar cell, resulting in a large loss of fill factor and energy conversion efficiency; when only O plasma is used as an oxygen source to prepare a tin dioxide layer of the same thickness in Comparative Application Example 2, the oxygen plasma will cause serious damage to the perovskite surface during the deposition process, thereby greatly reducing the performance of the perovskite absorption layer and the overall performance of the perovskite solar cell; when only O3 is used as an oxygen source to prepare a tin dioxide layer of the same thickness in Comparative Application Example 3, due to the strong oxidizing property of O3, it will affect the surface of the oxide perovskite, thereby greatly reducing the performance of the perovskite absorption layer and the overall performance of the perovskite solar cell.
[0118] In summary, the composite tin dioxide layer of the present invention combines tin dioxide layers deposited using different oxygen sources, which makes up for the film structure defects and physical and chemical property disadvantages of the tin dioxide layer deposited using a single oxygen source. After the combination, the advantages of each tin dioxide layer can be taken into account. The complementary advantages improve the film quality of the prepared composite tin dioxide layer, and when used in perovskite solar cells, it can further improve the open circuit voltage, fill factor, energy conversion efficiency and other performance.
[0119] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a composite tin dioxide layer for a perovskite cell, characterized in that: The preparation method comprises the following steps: depositing at least two stacked tin dioxide layers by atomic layer deposition technology; The deposition raw materials of each tin dioxide layer independently include an oxygen source and a tin source, and the oxygen sources used by two adjacent tin dioxide layers are different in type; in the composite tin dioxide layer, the thickness of each tin dioxide layer is independently ≥1 nm.
2. The preparation method according to claim 1, characterized in that: The oxygen source includes any one of water, ozone or plasma activated oxygen; Preferably, when depositing the first tin dioxide layer, the oxygen source is water; Preferably, when depositing at least three stacked tin dioxide layers, the deposition of three tin dioxide layers is considered as one group of deposition processes. When the number of the deposition groups is 1, the type of oxygen source used in each tin dioxide layer is different. When the number of the deposition groups is greater than 1, the type of oxygen source used in each tin dioxide layer is different, and the types of oxygen sources used in two adjacent tin dioxide layers in each group are different. Preferably, the tin source comprises any one of alkyl tin, tin alkoxide or tetrakis(dimethylamino)tin or a combination of at least two thereof, preferably tetrakis(dimethylamino)tin; Preferably, in the composite tin dioxide layer, the thickness of each layer is independently 2nm-15nm; Preferably, the total thickness of the composite tin dioxide layer is 10 nm-40 nm.
3. The preparation method according to claim 1 or 2, characterized in that: The step of depositing at least two stacked tin dioxide layers by atomic layer deposition technology comprises: The tin source is introduced and purged with an inert gas, and then the oxygen source is introduced and purged with an inert gas, so that the tin source and the oxygen source react. This is one cycle. After multiple cycles, the first tin dioxide layer is obtained. Then the type of the oxygen source is replaced and the above process is repeated to obtain at least two stacked tin dioxide layers.
4. The preparation method according to claim 3, characterized in that: The tin source is introduced through the inert gas as a carrier gas, and the flow rate of the carrier gas is 50sccm-250sccm; Preferably, the tin source is introduced for a time of 0.1s-0.6s; Preferably, the oxygen source is introduced through the inert gas as a carrier gas, and the flow rate of the carrier gas is 50 sccm-250 sccm; Preferably, when the oxygen source is water, the water is introduced for a time of 0.2s-1.8s; Preferably, when ozone is used as the oxygen source, the ozone is introduced for 4s-12s; Preferably, when the oxygen source is plasma-activated oxygen, the introduction time of the plasma-activated oxygen is 4s-12s; Preferably, the number of the multiple cycles is 10 to 150 times; Preferably, the flow rate of the inert gas purge is 50 sccm-250 sccm; Preferably, the inert gas purge time is 5s-15s; Preferably, the inert gas comprises argon or nitrogen.
5. A composite tin dioxide layer, characterized in that: The composite tin dioxide layer is prepared according to the preparation method according to any one of claims 1 to 4.
6. A perovskite solar cell buffer layer, characterized in that: The perovskite solar cell buffer layer comprises the composite tin dioxide layer as claimed in claim 5.
7. A perovskite solar cell electron transport layer, characterized in that: The perovskite solar cell electron transport layer comprises the composite tin dioxide layer as claimed in claim 5.
8. A perovskite solar cell, characterized in that: The perovskite solar cell comprises the perovskite solar cell buffer layer according to claim 6 and / or the perovskite solar cell electron transport layer according to claim 7.
9. The perovskite solar cell according to claim 8, characterized in that: The perovskite solar cell includes subcells connected in series.
10. The perovskite solar cell according to claim 9, characterized in that: The subcell comprises a cathode conductive substrate, a hole transport layer, a perovskite light absorbing layer, an electron transport layer, a buffer layer and a conductive anode layer which are stacked in sequence, and the buffer layer comprises the perovskite solar cell buffer layer as claimed in claim 6.